Transactional Leadership, Motivation and Employee Performance - Ni Putu Diah Wahyuni; Dian Alfia Purwandari; Tantri Yanuar Rahmat Syah (Journal of Multidisciplinary Academic, 2019)
This study aimed to explain and analyze the influence of transactional leadership on employee performance through motivation as an intervening variable. This research was conducted over manufacturing company. Here, we use 140 correspondents to take the data observation. In order to analyze the data hypotheses, we use exploratory method over AMOS software. The results shows that the significant and positive relationship exists between transactional leadership on motivation, motivation on employee performance, and transactional leadership on employee performance with motivation as intervening have positive correlation. If the transactional leadership and organizational culture are supported by high work motivation, a company will be able to improve performance action